Pregnancy Intention and Associated Maternal Behaviors during Pregnancy among Pregnant Women in Gamo-Goffa Zone, Southern Ethiopia - Gergiso, Kabtamu Tolosie; Shimbre , Mulugeta Shegaze; Gadore, Tesfaye Feleke; Hebo, Sultan Hussen (Ethiopian Journal of Reproductive Health, 2020)
Introduction: Pregnancy is a happy event for women when it is intended. Instead, an unintended pregnancy leads the mother to unhealthy behaviors which in turn causes maternal mortality and morbidity. But limited evidence exists on the effects of unintended pregnancy on maternal behaviors during pregnancy in Ethiopia particularly in the study area. Therefore, this study aimed to identify the effect of pregnancy intention on maternal behaviors during pregnancy among pregnant women in Gamo-Goffa Zone, Southern Ethiopia. Methods: Community-based cross-sectional study design employed in Gamo-Goffa Zone from March, 13 to April 13, 2017. Using multi-stage stratified sampling technique 770 pregnant women were selected and enrolled in the study. The logistic regression was performed to identify the independent effect of pregnancy intention on maternal behaviors. Results: More than one-third (36.2%) study participants experienced an unintended pregnancy. Women with unintended pregnancy were 69% times less likely to receive antenatal care (AOR = 0.31, 95% CI (0.21 – 0.46)); four times more likely to initiation antenatal care late (AOR = 4.40, 95% CI (1.70 – 11.40)) and three times more likely to use the substance (AOR = 3.01, 95% CI (1.81 – 5.02)) during pregnancy. Conclusion: Women with unintended pregnancy are less likely to receive recommended antenatal care and more likely to engage in risky behaviors. Therefore, besides promotion on the utilization of effective contraception to prevent unintended pregnancy, behavioral change communications directed toward increasing utilization of antenatal care and minimization of risky behaviors are recommended to attain healthy behaviors during any type of pregnancy.